THE TAREKAT SAMMANIYAH IN THE SULTANATE OF BUTON, A STUDY OF THE SULTANATE MANUSCRIPT - Falah Sabirin (UIN Syarif Hidayatullah Jakarta, 2022)
AbstractThis article discusses the genealogy of sanad and the Tarekat Sammaniyah teaching style in the Sultanate of Buton. This study found that in the Buton sultanate, there was a side of the Tarekat Sammaniyah which had several features and shortcomings. First, Muhammad ‘Aydru, a sultan who studied the the Tarekat Sammaniyah from a Mekkah scholar. Second, the spread of the Tarekat Sammaniyah only developed among the nobles in the Buton Sultanate. The teaching style of the Tarekat Sammaniyah is not much different from the primary source text, specifically, al-Nafahat al-Ilahiyah by Muhammad bin 'Abd al-Karim al-Samman. This shows a strong indication of the interaction between 'Aydrus and local Sammaniyah role models through the lineage of 'Abd al-Samad. However, there are several traditions of remembrance that are slightly different from the Sammaniyah taught by 'Abd al-Samad. This can be seen when 'Aydrus puts recitation of tahlil at an advanced level, while 'Abd al-Samad makes remembrance at the beginner level. However, there was no difference at all in the procedures for remembrance of the adab.AbstrakArtikel ini membahas tentang sisilah sanad dan corak ajaran Tarekat Sammaniyah di Kesultanan Buton. Dalam penelitian ini ditemukan bahwa di kesultanan Buton terdapat sisilah Tarekat Sammaniyah memiliki beberapa keistimewaan juga menjadi kekurangan. Pertama, Muhammad ‘Aydrus yang seorang sultan mempelajari Tarekat Sammaniyah kepada seorang ulama Makkah. Kedua, penyebaran tarekat Sammaniyah hanya berkembang di kalangan bangsawan yang berada di Kesultanan Buton. Adapun corak ajaran Tarekat Sammaniyah tidak jauh berbeda dengan teks sumber utamanya, yaitu al-Nafahat al-Ilahiyah karya Muhammad bin ‘Abd al-Karim al-Samman. Hal ini menunjukkan adanya indikasi kuat interaksi antara ‘Aydrus dengan tokoh-tokoh Sammaniyah lokal melalui jalur silsilah ‘Abd al-Samad. Namun ada beberapa tradisi zikir yang sedikit berbeda dengan Sammaniyah yang diajarkan ‘Abd al-Samad. Ini terlihat saat ‘Aydrus menempatkan zikir tahlil pada tingkatan lanjutan, sedangkan ‘Abd al-Samad menjadikan zikir pada tingkatan pemula. Namun pada akhirnya tidak ada perbedaan sama sekali pada tatacara berzikir padab-adab.